First Clinical Results of Hyperopic Eyes Treated with a New Ablative Solid-State Laser - Bojan Pajic; Zeljka Cvejic; Anna Schroeter; Valentin Pajic; Anthia Papazoglou; Brigitte Pajic-Eggspuehler (Medicina)
Investigation and evaluation of the first clinical results of the new ablative solid-state laser (AQUARIUZ) regarding clinical outcome, inclusively higher-order aberration and safety. In this case report, three hyperopic patients with six eyes were treated with the new ablative solid-state laser (AQUARIUZ). The LASIK incisions are cut with the Ziemer LDV Z8. All patients were followed for 6 months postoperatively. The treated hyperopia ranged from +0.5 D to +2.75 D. Emmetropia of 0 D was found in four eyes after 6 months. In two eyes there was a slight myopia of −0.25 D each, which is also considered emmetropia according to the definition. The aspherically optimized profile of the ablative solid-state laser did not induce a higher-order aberration or spherical aberration in any eye. No eye lost CDVA or UDVA lines after the follow-up period. The safety index was 1 in five eyes and 1.25 in one eye. The findings demonstrate a high level of precision and treatment safety with the new ablative solid-state laser.